PENYULUHAN KESEHATAN REPRODUKSI DALAM UPAYA PEMBANGUNAN KESEHATAN REMAJA DI DESA SUKAMUKTI KABUPATEN GARUT - Atu Setiati; Ayu Rahadianti; Tami Sri Rahayu; Qori Alya M; Bela Salsabila (LPPM Universitas Abdurrab, 2023)
Sukamukti Village is the village chosen to get the â€œPower To Youthâ€ Program by Garut Regency because of the high rate of child marriage and dispensation of marriage. This is an urgent problem because the impact will be detrimental to youth as the nation's next generation because they are at risk of having poor quality reproductive health. In an effort to build reproductive health, there must be activities to support changing people's views regarding the importance of reproductive health. The aim of reproductive health counseling is to increase insight and knowledge so as to increase youth awareness of the importance of maintaining reproductive health and reducing the number of child marriages in Sukamukti Village. Through the Participatory Rural Appraisal (PRA) method to analyze youth problems by the SEMAK Foundation, it can be seen from the high number of child marriages and requests for dispensation from marriage at KUA due to the lack of knowledge of parents and youth. The results of this service have made the Banyuresmi Youth Communication Forum in Sukamukti Village more appreciated by the government and the community, obtained legality by the village government as a CSO that focuses on adolescent health, and can be productive through youth posyandu. Suggestions for the village government are to give authority to the Sukamukti youth group to be able to participate in making policies specifically for youth in supporting equality, welfare, fulfilling children's basic rights in maintaining reproductive health.